Limites e possibilidades do uso da webquest no ensino de física - Silva, Willians Gavioli da (2015)
This research aims to check the limits and potential use of WebQuest in support oriented research tool on the Internet in a public school in São Paulo State. The research refers to the implementation and development of a WebQuest, applied to the third year of high school students from a public school located in Caconde entitled: Calculating Costs of Electricity. Through targeted research provided by WebQuest, prepared by research professor, students conducted research on energy consumption consumed by the use of devices via the magnitudes involved with them: energy, power, voltage, electric current and the operating time of equipment used in a residence. The survey was conducted according to the practice developed in the classroom, a dental educational research methodology, which involved three times, which is the before, during and after the application of WebQuest, which were observed, registered to the data were analyzed. It was found that the WebQuest, used as a research tool in teaching using the Internet proved to be a great facilitator of information research, promoting a collaborative environment, the transformation of information into knowledge, and provide autonomy to students, with the focus, the active student, the research methodology and the teacher as mediator. How limits, it was observed that its use requires adequate space, availability of time needed to design and implementation, dedication by the students in carrying out research and care tasks and to establish that the WebQuest, is another resource available to promote the transformation of information into knowledge. The teacher should use it as an enriching feature of the educational environment, to promote the construction of knowledge through an active and critical role by both students and teachers.